Comparative efficacy of non-pharmacological interventions on fear of childbirth for pregnant women: a systematic review and network meta-analysis - Zhou, Juan; Zhu, Zhengting; Li, Ruoyu; Guo, Xiujing; Li, Dehua (Frontiers in Psychology, 2025)
ObjectiveTo explore effectiveness of non-pharmacological interventions in fear of childbirth.MethodsAll published literature were searched from three databases (Pubmed, Cochrane CENTRAL, and Web of Science) as of April 2024. The risk of bias of the included studies was assessed using the Cochrane Systematic Review Manual 2.0 bias risk assessment tool. The primary outcome was FOC, the secondary outcomes were depression, anxiety, stress, childbirth self-efficacy, and mode of delivery.ResultsThis study included 32 randomized controlled trials, involving 17 interventions and 3,187 pregnant women. Compared with usual care, cognitive-behavioral therapy (SMD = −1.62, 95%CI –2.47 to −0.66), haptonomy (SMD = −1.43, 95%CI –2.63 to −0.24), motivational interview (SMD = −1.35, 95%CI –2.35 to −0.35), counseling therapy (SMD = −1.08, 95%CI –1.91 to −0.25) statistically and significantly improved fear of childbirth in gestational period. Emotional freedom technique (SMD = −3.13, 95%CI –5.00 to −1.26), counseling therapy (SMD = −1.81, 95%CI –2.97 to −0.80), haptonomy (SMD = −1.78, 95%CI –2.89 to −0.66), cognitive-behavioral therapy (SMD = −1.42, 95%CI –2.53 to −0.32), motivational interview (SMD = −1.28, 95%CI –2.37 to −0.19) statistically and significantly improved fear of childbirth in postnatal period. The cluster analysis showed that emotional freedom technique, haptonomy, motivational interview, cognitive-behavioral therapy, counseling therapy were considered to be more effective non-pharmacological interventions.ConclusionSeveral non-pharmacological interventions are promising in the daily care of pregnant women with fear of childbirth. Healthcare professionals should be encouraged to apply these non-pharmacological interventions for informal caregivers of pregnant women with fear of childbirth.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO, CRD42024536944.